Methods of information protection based on quantum image steganography - Fediushyn, O.I.; Holovko, Y.V.; Smirnov, A.O.; Sukhoteplyi, V.M.; Chechui, O.V. (Radiotekhnika, 2024)
The purpose of the article is to study information protection methods based on quantum image steganography. Traditional image protection techniques have limitations in terms of resilience and reliability. The use of quantum computing, particularly the NEQR model, offers significant advantages in enhancing the security and efficiency of watermarks and steganography. The article analyzes existing approaches to image representation in quantum states and demonstrates their superiority in digital image protection. A simulation of steganography using quantum algorithms is presented, showing improved information security. The article will be useful for information security professionals involved in data protection using modern quantum technologies.